Norm of the Bergman Projection - Kalaj, David; Marković, Marijan (MATHEMATICA SCANDINAVICA, 2014)
This paper deals with the the norm of the weighted Bergman projection operator P_α:L^∞(B)→B where α > - 1 and B is the Bloch space of the unit ball B of the C^n. We consider two Bloch norms, the standard Bloch norm and invariant norm w.r.t. automorphisms of the unit ball. Our work contains as a special case the main result of the recent paper [6].